Inflammatory bowel diseases in pregnant women - current state of knowledge - Góra, Karolina; Zdziennicki, Wojciech; Zimnicki, Patryk; Lato, Marta; Iberszer, Konrad; Litwiniuk, Maria; Zaniuk, Marcin; Hurkała, Kamil; Antonik, Dominika; Denys, Barbara (Journal of Education, Health and Sport, 2023)
Introduction and objective: Inflammatory bowel diseases (IBD) are a group of chronic inflammatory diseases. Usually they affect young people, often during pregnancy. Insufficient knowledge about the evolution of the disease during pregnancy, as well as the effects of drugs used, often result in resignation from motherhood, while unfamiliarity with the principles of therapy or discontinuation of treatment during pregnancy are significant causes of obstetric failures. The aim of the study was to summarize the data available in the literature as well as recent reports, to enable a better understanding of the disease and care of pregnant women with IBD. Materials and methods: The literature was reviewed in the Pubmed database, in the Via Medica Journals database, and in the guidelines of the Polish Society of Gastroenterology with the use of keywords. State of knowledge: 85% of women with IBD become pregnant without complications, but the inflammation has a negative impact on both the course of pregnancy and the fetus itself. Complications, which often depend on the activity of the disease before and during pregnancy, may occur: i.e. premature birth, inadequate fetal weight, miscarriage, as well as complications in the child itself and flares of the underlying disease. Therefore, it is important to know rules of safe pharmacotherapy that apply before and after pregnancy in order to prevent the negative effects of the disease. Special situations caused by IBD, i.e. surgical or endoscopic procedures, can be successfully performed in pregnant patients with the observance of certain rules. Conclusions: Understanding the causes of complications that may occur in the patient and the child allows them to be prevented. Both for the mother's health and for a positive course of pregnancy, education and pregnancy planning, preceded by the change of medications to safe for the fetus, are extremely important.